A single-session Mindfulness-Based Swinging Technique vs. cognitive disputation intervention among women with breast cancer: A pilot randomised controlled study examining the efficacy at 8-week follow-up - Bahcivan, Ozan; Gutierrez-Maldonado, Jose; Estapé, Tania (Frontiers in Psychology, 2022)
Objective: Previously Mindfulness-Based Swinging Technique (MBST)'s immediate efficacy for overcoming psychological concerns have recently received empirical support, yet its longer-term efficacy needed to be evaluated among women with breast cancer. The objective of this study was to assess and report the efficacy of MBST intervention among breast cancer patients for hopelessness, anxiety, depression, self-efficacy, oxygen (SpO2) intensity as well as heart rate-beats per minute(HR-bpm) at 8-week period. Method: The State Trait Anxiety Inventory, The Emotion Thermometer, Hospital Anxiety and Depression Scale, Self-Efficacy for Managing Chronic Disease, and Beck’s Hopelessness Scale were used for assessing the intervention’s outcome. 149 BC-patients were randomly assigned into two groups (equal-mean-age, p=0.262). The participants in the Control-Group (CG, n=73) received the Cognitive Behavioural Therapy (CBT)-Cognitive-Disputation (CBT-CD) for 20 mins, and Intervention-Group (IG, n=76) received MBST intervention. No additional psychological interventions were given between week-1 and week-8. Result: Outcomes of the 8-week post-treatment follow-up exhibited significantly higher-improvements in all evaluated-measurements for CG, and some for IG with large-effect-size in the following: anxiety (CG p<0.05, r=0.57; IG p<0.05, r=0.44) and depression-levels (CG p<0.05, r=0.43). It increased self-efficacy for managing-disease (CG p<0.05, r=0.49; IG p<0.05, r=0,41) as-well-as hopefulness (CG p<0.05, r=0.59; IG p<0.05, r=0.46) and saturation-levels measured by pulse-meter/oximeter (CG p<0.05, r=0.49; IG p<0.05, r=0.32). Conclusions: Both CBT-CD and MBST have been found to be efficacious interventions to shorten the psychotherapy duration for reducing clinical anxiety and hopelessness as well as increase self-efficacy for BC-women. This may have a distinct clinical importance for supporting BC patient’s adherence-to-treatment since CBT-CD could be an alternative technique to MBST as a brief intervention. In future studies, the effectiveness of MBST through adapting to Virtual-Reality and other online delivery methods should be examined.